PENGAWASAN KENDARAAN OVER DIMENSION OVER LOADING (ODOL) DI JALAN LINTAS INDRAGIRI HULU - Gusvita Maya Sari; Zaili Rusli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Supervision of Over dimension over loading Vehicles on the Indragiri Hulu Cross Road is a step taken by the Riau Provincial Transportation Service to anticipate and prevent violations in driving, especially on Over dimension over loading vehicles. The purpose of this study is to find out how the Over dimension over loading Vehicle Supervision works on the Indragiri Hulu Highway, as well as to determine the inhibiting factors of the implementation of supervision. This study uses the theory of supervision by Manullang (2015) which is seen based on the time of its implementation in the form of preventive supervision and repressive supervision. This study uses a qualitative research type with a descriptive approach. The results of the research from Over dimension over loading Vehicle Supervision have not run optimally. The inhibiting factor in the implementation of Over dimension over loading Vehicle Supervision is the lack of budget given to carry out field supervision activities and the lack of understanding of drivers in driving which causes less than optimal implementation of Over dimension over loading Vehicle Supervision on the Indragiri Hulu Highway. Keywords: Supervision, Over Dimension, Over Loading